The Sino-Japanese War of 1894–1895: Partially decrypted. Issue 2 (4th March 2018) - Nedved, Gregory J.
ABSTRACT: Cryptology during the Sino-Japanese War of 1894–1895 is a topic hardly explored, especially by Westerners. We now know that the Japanese military and diplomatic successes were aided by codebreaking. This article covers what is known about the cryptology employed during the war, to include rare information coming from Chinese language sources (most sources on the cryptologic role in the war had heretofore been Japanese). The author cautions that this topic is still a work in progress with more to uncover. He is particularly excited about some new Chinese language findings, awaiting proper translation.